Neuronal gating of tactile input and sleep in 10-month-old infants at typical and elevated likelihood for autism spectrum disorder - De Laet, Anna; Piccardi, Elena Serena; Begum-Ali, Jannath; Charman, Tony; Johnson, Mark H.; Jones, Emily J. H.; Bedford, Rachael; Gliga, Teodora; Agyapong, Mary; Bazelmans, Tessel; Dafner, Leila; Ersoy, Mutluhan; et al. (Springer Science and Business Media LLC, 2022)
AbstractSleep problems in Autism Spectrum Disorder (ASD) emerge early in development, yet the origin remains unclear. Here, we characterise developmental trajectories in sleep onset latency (SOL) and night awakenings in infants at elevated likelihood (EL) for ASD (who have an older sibling with ASD) and infants at typical likelihood (TL) for ASD. Further, we test whether the ability to gate tactile input, using an EEG tactile suppression index (TSI), associates with variation in SOL and night awakenings. Parent-reported night awakenings and SOL from 124 infants (97 at EL for ASD) at 5, 10 and 14 months were analyzed using generalized estimating equations. Compared to TL infants, infants at EL had significantly more awakenings and longer SOL at 10 and 14 months. The TSI predicted SOL concurrently at 10 months, independent of ASD likelihood status, but not longitudinally at 14 months. The TSI did not predict night awakenings concurrently or longitudinally. These results imply that infants at EL for ASD wake up more frequently during the night and take longer to fall asleep from 10 months of age. At 10 months, sensory gating predicts SOL, but not night awakenings, suggesting sensory gating differentially affects neural mechanisms of sleep initiation and maintenance.
Keywords: Sleep Wake Disorders; Autism Spectrum Disorder; Science; Siblings; Q; R; article; Infant; Sleep Latency; /631/378/3917; Article; Medicine; /631/378/1385; Humans; /631/477; Sleep